2015
DOI: 10.1186/s12885-015-1474-8
|View full text |Cite
|
Sign up to set email alerts
|

Combined inhibition of the cell cycle related proteins Wee1 and Chk1/2 induces synergistic anti-cancer effect in melanoma

Abstract: BackgroundMalignant melanoma has an increasing incidence rate and the metastatic disease is notoriously resistant to standard chemotherapy. Loss of cell cycle checkpoints is frequently found in many cancer types and makes the cells reliant on compensatory mechanisms to control progression. This feature may be exploited in therapy, and kinases involved in checkpoint regulation, such as Wee1 and Chk1/2, have thus become attractive therapeutic targets.MethodsIn the present study we combined a Wee1 inhibitor (MK17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
24
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 56 publications
(66 reference statements)
6
24
0
2
Order By: Relevance
“…Since the primary clinical necessity in HPV(+) HNSCC currently is to safely deintensify treatment, dual inhibition with reduced doses may be a viable approach but as a new regimen would need to be carefully studied in clinical trials focusing on both toxicity and efficacy. A number of recent publications have reported synergistic effects when combining Chk1 and Wee1 inhibition in cells of various tumor entities in vitro and in xenograft models, and some also reported an activation of Chk1 upon Wee1 inhibition [25][26][27][28][29][30][31][32]. Dual inhibition induced replication arrest and DNA damage, apoptosis, premature mitosis and a reduction of proliferation and viability.…”
Section: Discussionmentioning
confidence: 97%
“…Since the primary clinical necessity in HPV(+) HNSCC currently is to safely deintensify treatment, dual inhibition with reduced doses may be a viable approach but as a new regimen would need to be carefully studied in clinical trials focusing on both toxicity and efficacy. A number of recent publications have reported synergistic effects when combining Chk1 and Wee1 inhibition in cells of various tumor entities in vitro and in xenograft models, and some also reported an activation of Chk1 upon Wee1 inhibition [25][26][27][28][29][30][31][32]. Dual inhibition induced replication arrest and DNA damage, apoptosis, premature mitosis and a reduction of proliferation and viability.…”
Section: Discussionmentioning
confidence: 97%
“…In previous studies, AZD1775 has been shown to have a synergistic effect in DNA damage–based therapeutics by inducing unscheduled mitosis and eventually resulting in apoptosis in various cancers, such as melanoma, glioblastoma, and pancreatic cancer [2830]. We also assessed the clinical potential of AZD1775 when combined with anti-cancer drugs, such as 5-FU (a DNA damage agent) and Paclitaxel (a mitotic inhibitor).…”
Section: Discussionmentioning
confidence: 99%
“…To solve this vexing drug resistance problem, combination therapy has been the solution over the last two decades, owing to their synergistic effects seen in some trials [4][5][6]. Although drug resistance is a common phenomenon in chemotherapy, the puzzling mechanism involving complicated signaling pathways is not entirely clear.…”
mentioning
confidence: 99%